ASSESS THE RISK OF CONSTIPATION AMONG PATIENTS UNDERGOING ABDOMINAL SURGERY - Ms. Monali Walke, Ms. Sheetal Sakharkar (International Journal of Modern Agriculture, 2020)
Background: Constipation is becoming main problems with related of modifiable lifestyle which mainly disturbing health of the person. Constipation can found at any age due change in life style , eating habits , fast foods, lack of exercise, lack of time for drinking water this are mainly reason of getting constipation. Constipation suffering person can mostly have this symptom which are abdominal and rectal pain, bloating, forcing, bowel movement stop or rare, hard stool, quantity of stool is less, difficulty in defecation, frequency of stool is less than three par weeks. Objective :In this study planned to assess the risk of constipation among undergoing abdominal surgery patients and also associate the risk of constipation among undergoing abdominal surgery patients with selected demographic variables Methodology: It is descriptive research design used in this research study conducted on patients are undergoing among abdominal surgery. Unlikely purposeful sampling technique used to select samples for analysis. This research study included 85 patients of AVBRH Rural hospital Sawangi (m). Patients must select according to requirements for inclusion and exclusion. For this study, patients who were undergoing abdominal surgery like as stomach, gall bladder, liver, spleen, pancreas, small intestine, and large intestine would mainly take. Age criteria above 18-year male, female can be the sample for the study. Expected Results: Outcome includes risk of constipation on patients undergoing abdominal surgery patients for the study are Low risk , moderate risk and severe risk of constipation by using risk assessment constipation scale. Ethics approval was obtained from (DMIMS(DU)/IEC/DEC-2019/8641). The conclusion will be drawn from the results. Conclusion: Conclusion will be drawn from the statistical analysis.